Predicting prostate cancer many years before diagnosis: how and why? - Vickers, A; Lilja, H (2012)
Evidence of reduced prostate cancer mortality from randomized trials in Europe supports early detection of prostate cancer with prostate-specific antigen (PSA). Yet PSA screening has generated considerable controversy: it is far from clear that the benefits outweigh risks, in terms of overdiagnosis and overtreatment. One way to shift the ratio of benefits to harm is to focus on men at highest risk, who have more to benefit than average. Neither family history nor any of the currently identified genomic markers offer sufficient risk stratification for practical use. However, there is considerable evidence that the levels of PSA in blood are strongly prognostic of the long-term risk of aggressive prostate cancer. Specifically, it is difficult to justify continuing to screen men aged 60 or older if they have a PSA less than 1 or 2 ng/ml; for men 45-60, intervals between PSA tests can be based on PSA levels, with 2-4-year retesting interval for men with PSA of 1 ng/ml or higher, and tests every 6-8 years for men with PSA <1 ng/ml. Men with the top 10% of PSAs at a young age (PSA ~1.5 ng/ml or higher below 50) are at particularly high risk and should be subject to intensive monitoring.